Updated seismic fragility functions for cold-formed steel framed shear walls per FEMA P-58 methodology. (1st October 2021) - Haghpanah, Fardad; Schafer, Benjamin W.
Highlights: Updated fragility functions for CFS framed shear walls based on a wider database. Separate functions for different wood sheathing materials. Separate functions for flat straps with different steel grades. Separate functions for walls meeting the requirements per AISI S400. Two application examples for CFS framed shear wall damage assessment. Abstract: Performance-based earthquake engineering (PBEE) provides a robust alternative to traditional earthquake design. PBEE enables engineers to estimate expected damage, repair costs, and economic losses due to downtime for a candidate design, potentially leading to novel new designs or retrofit solutions. With the increasing application of light-frame structural systems, such as cold-formed steel (CFS) panels, in residential and commercial construction, it is necessary to develop and employ fragility functions for these systems to enable PBEE. In this regard, a set of fragility functions was previously developed by researchers based on a series of monotonic and cyclic tests for CFS framed shear walls with wood structural panel sheathing, flat strap X-bracing, and steel sheet sheathing. Recently, the senior author has led in the development of a large database of CFS framed shear wall tests, including 617 monotonic and cyclic tests conducted in the last 20 years from 25 primary sources. Based on the wider database, the fragility functions for CFS framed shear walls are re-evaluated. The developed fragility functions provide updated knowledge for application of PBEE per the FEMA P-58 methodology and are recommended for future use.